Karakterisasi Fenotipik dan Genotipik Tanaman Anggrek Transgenik Phalaenopsis amabilis (L.) Blume Pembawa Konstruksi T-DNA UbiPro::PaFT - , Ida Ayu Purnama Bestari ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The moth orchid Phalaenopsis amabilis (L.) Blume is a wild orchid of Indonesia with high economic value, easily cultivated, but need a long period for flowering after the age of 3 years. The genetic transformation has been carried out on protocorm P. amabilis by Mercuriani (2011) with the insertion orthologous gene Flowering Locus T of Phalaenopsis amabilis (PaFT) via Agrobacterium tumefaciens strain GV3101. The 45 candidates of transgenic protocorm have been confirmed that carrying T-DNA construction UbiPro::PaFT. Binary vector is pGAS102, that containing HPT gene. Selection for transforman performed on medium New Phalaenopsis (NP) added with hygromycin 10 mg/L. DNA genome of transforman candidates were further amplified with Ubi (forward) and T-Nos (reverse) primers, specific primers for HPT gene and deg PaFT can be amplified about 1137 bp, 810 bp and 533 bp DNA respectively, Analysis of mRNA accumulation was also carried out for the detection of activity PaFT gene (induction of flowering gene) and POH1 gene (bud formation gene) using RT-PCR method. Phenotypic analysis was conducted to determine the effect of PaFT genes on orchids transgenic, by counting the number of shoots, the number of leaves, leaf length, number of roots, root length, and the development of transgenic plants. The data show that insertion of T-DNA containing UbiPro::PaFT induced the growth of roots and multishoots. Accumulation of mRNA transgene UbiPro::PaFT was 533 bp in the length, whereas te accumulation of endogenous PaFT mRNA in non transforman plants was 700 bp, In vitro flowering has not occurred yet, it might be related to POH1 gene expression or unknown process magnitude of POH1 gene expression working redundancy with PaFT gene expression.